Characteristic differences in barrier and hygroscopic properties between normal and cosmetic dry skin. II. Depth profile of natural moisturizing factor and cohesivity. (29th March 2014) - Feng, L.; Chandar, P.; Lu, N.; Vincent, C.; Bajor, J.; McGuiness, H.
Synopsis Objective In a previous paper (Lu et al., International Journal of Cosmetic Science, in press), we reported that in comparison with normal skin, cosmetic dry skin characteristically has a thicker stratum corneum (SC) with weaker barrier quality. Our goal here was to obtain a more complete picture of the difference between normal and cosmetic dry skin, by further analysing the data collected from the same clinical study to address two additional aspects of skin: the amount and depth profile of natural moisturizing factor (NMF) and the cohesivity of the SC. Method The SC samples were collected by sequential tape stripping in a clinical study consisting of 64 healthy Caucasian female subjects with either normal or cosmetic dry skin. Protein and free amino acids (FAA) on tape strips were extracted and analysed using high‐throughput methods. The level of pyrrolidone carboxylic acid (PCA), the prominent component of NMF, was detected using HPLC analysis. Results It was found that dry skin had significantly lower ratios of FAA/protein and PCA/protein across the stripped SC depth, corresponding to a lower hydration level compared with the normal skin. Our results indicated that filaggrin to FAA hydrolysis occurred deeper in dry skin and at a lower level compared with normal skin. In addition, the mass of proteins stripped from dry skin subjects was significantly higher than that from the normal skin counterpart, especially for the first 10–12 tape strips. Conclusion Our results showed that, compared with normal skin, cosmetic dry skin had a lower NMF level across the SC depth and a lower cohesivity. Such results suggested that NMF levels are critical for cosmetic skin conditions, and lower NMF production may be associated with dry skin. In addition, the NMF level and its depth profile and the SC cohesivity are useful clinical end points for assessing the efficacy of dry skin treatments such as skin moisturizers.